Characterization of Polyol Synthesized from Epoxidized Palm Oil Using Fourier Transform Infra-Red and Nuclear Magnetic Resonance - Rahmat, A. R.; Wan Tajulruddin, W. N.; Mohd Yusof, Z. A.; Fakhari, A. (Journal of Advanced Research in Applied Mechanics, 2020)
In this present study, ring opening polymerization (ROP) method has been used to prepare a bio-based polyol (PEPO) from epoxidized palm oil (EPO). This reaction was carried out in the presence of fluoroantimonic acid hexahydrate (HSbF6·6H2O) as a catalyst at certain concentration. The synthesized polyol was characterized with regard to its structural properties by fourier transform infra-red (FTIR) and nuclear magnetic resonance (NMR). The findings of this study revealed that the epoxy group presents in epoxidized palm oil (EPO) at 833 cm-1 disappeared in the synthesized polyol while the hydroxyl group presents with the emergence of peak at 3522 cm-1 in the FTIR spectrum. Based on NMR, the disappearance of epoxy ring group at 2.8-3.0 ppm indicates the completely reacted oxirane ring with the presence of signal at 3.7 ppm corresponded to hydroxyl group.